EFEKTIVITAS KEBIJAKAN SERTIFIKASI GURU (Suatu Studi di SMA Negeri I Manado) - Veronika, Stevi Wanda (Sam Ratulangi University, 2014)
Teaching license is a certification procces for teachers who have the requirements, like an academic qualifications and professional competence of teachers. So, the teaching license policy should increase the professionalism of the teachers. But the implementation, it doesn't work, the teaching license has so many weakness. Based from it, this research was conducted for answer the question